Oscillations in microtubule polymerization: the rate of GTP regeneration on tubulin controls the period. - Melki, R (1988)
The essential reactions involved in the oscillatory kinetics of microtubule polymerization have been investigated. The rate of GDP dissociation from tubulin decreased cooperatively upon increasing tubulin concentration above 20 microM, consistent with the formation of GDP oligomers whose dissociation is rate limiting in nucleotide exchange. The apparent rate constant for nucleotide exchange at high tubulin concentration was 0.02 s-1 at 37 degrees C, which is the exact value needed in previous theoretical simulations to obtain oscillations with the real period of 70-80 s. A glass filter assay separating microtubules from oligomers and tubulin allowed nucleotide bound to non-microtubular tubulin during the oscillations to be monitored. In agreement with nucleotide exchange data, tubulin-bound GDP was found to oscillate in antiphase with microtubules. By varying the concentration of an enzymatic GTP-regenerating system, we could demonstrate that the period of the oscillations is directly controlled by the rate at which GTP is regenerated on tubulin, and oscillations can be observed under conditions where the dissociation of oligomers is no longer rate limiting. The possible physiological significance of GTP-regenerating systems in establishing synchrony in a microtubule population is evoked. The present data confirm and extend the model that we previously proposed to account for the oscillations.